Knowledge Level of Nurses about Hospital Triage: A systematic review study - Amir Hossein Goudarzian; Majid Ghorbanzadeh (ACHSM, 2023)
Objective: Triage prioritizes patient care based on the severity of the injury and aims to facilitate the best possible recovery for the majority of individuals within the shortest possible timeframe. This concept holds paramount importance in the realm of emergency care. The objective of this study was to assess the knowledge level of triage nurses working in hospitals. Methods: This systematic review study encompassed an extensive analysis of relevant literature, drawing from international databases such as PubMed, Scopus, Web of Knowledge, and Google Scholar, as well as Iranian databases including SID, Magiran. The search spanned the period from 1980 to 2023. Results: In the present study, 22 articles were selected for data extraction. Across all these articles, it was consistently observed that the knowledge level of the nurses ranged from low to moderate. Furthermore, two interventional studies reported a notable increase in knowledge levels among nurses following training. Conclusion: Based on the findings from multiple studies, it is evident that the knowledge level of triage nurses generally falls within the low to moderate range. Consequently, it is advisable to conduct further studies in a similar vein and implement necessary actions to address this issue.